2021
DOI: 10.1186/s13395-021-00265-6
|View full text |Cite
|
Sign up to set email alerts
|

Origins, potency, and heterogeneity of skeletal muscle fibro-adipogenic progenitors—time for new definitions

Abstract: Striated muscle is a highly plastic and regenerative organ that regulates body movement, temperature, and metabolism—all the functions needed for an individual’s health and well-being. The muscle connective tissue’s main components are the extracellular matrix and its resident stromal cells, which continuously reshape it in embryonic development, homeostasis, and regeneration. Fibro-adipogenic progenitors are enigmatic and transformative muscle-resident interstitial cells with mesenchymal stem/stromal cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 224 publications
2
87
0
2
Order By: Relevance
“…This may be a reflection of the complex tissue changes that occur during disease progression as the earliest RNA microarray studies in FSHD already identified a transcriptional dysregulation of vascular smooth muscle or endothelial cell genes 46 , 47 . Finally, we observed an increase of both defined fibro-adipogenic progenitor cell types (FAPs), which corresponds with the role for FAPs in response to muscle inflammation, regeneration and repair 48 . Of note, FAPs have been described to be increased after DUX4 expression in an inducible DUX4 mouse model, and FAPs may play a role in muscle fibrosis and fat replacement in FSHD 49 .…”
Section: Resultssupporting
confidence: 74%
“…This may be a reflection of the complex tissue changes that occur during disease progression as the earliest RNA microarray studies in FSHD already identified a transcriptional dysregulation of vascular smooth muscle or endothelial cell genes 46 , 47 . Finally, we observed an increase of both defined fibro-adipogenic progenitor cell types (FAPs), which corresponds with the role for FAPs in response to muscle inflammation, regeneration and repair 48 . Of note, FAPs have been described to be increased after DUX4 expression in an inducible DUX4 mouse model, and FAPs may play a role in muscle fibrosis and fat replacement in FSHD 49 .…”
Section: Resultssupporting
confidence: 74%
“…The infiltration of healthy muscle tissue with fatty fibrosis is a prominent feature of Duchenne Muscular Dystrophy (DMD) and other neuromuscular diseases, as well as sarcopenia, obesity, and diabetes 1,2 . Although increased fat infiltration in these conditions is strongly associated with decreased muscle function, our knowledge of why and how intramuscular fat forms is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The developmental origin of FAPs has been comprehensively reviewed recently [ 21 , 22 ]. The seminal work of Kardon and colleagues in the early 2000s identified a population of TCF7L2/TCF4+ (transcription factor 4; also known as transcription factor 7 like 2; TCF7L2) cells arising from the mesoderm lateral plate in the chick and mouse [ 23 ].…”
Section: Faps Developmental Origin and Markersmentioning
confidence: 99%
“…FAPs are located in the interstitial space of resting [ 21 ] or regenerating skeletal muscle ( figure 2 ). They were initially described for their bi-potent ability to differentiate into fibrogenic or adipogenic cells, but not myogenic cells [ 15 , 17 ].…”
Section: Faps Characteristicsmentioning
confidence: 99%